El teletrabajo postpandemia: beneficios y retos - Batista Jiménez, Almudena (2023)
The implementation of remote working in Spain has been accelerated by the COVID-19 healthcare crisis. This situation, which has quickly become a reality, has given rise to significant legislative changes regarding post-pandemic remote working, which were undoubtably necessary given the few regulations that were in place. However, certain questions have arisen regarding interpretation which have yet to be fully resolved.This article analyzes the main benefits of working from home (such as flexibility and work-life balance), as well as its challenges for companies and workers. For example, the need to have timekeeping records, guarantee the right to digitally disconnect from work, ensure corporate control and occupational risk prevention. It also looks at some practical solutions that companies are applying.Finally, the article briefly examines the main features of international remote working and the legal issues involved in implementing it based on the current international regulations.